Crashworthiness study of a subway vehicle collision accident based on finite-element methods. Issue 2 (4th March 2021) - Wei, Liang; Zhang, Lele; Tong, Xin; Cui, Ke
Abstract: The investigation and reconstruction are fundamental to enable designers to improve the subway vehicle's crashworthiness. In this paper, a crashworthiness study of a subway vehicle collision accident in Beijing was conducted. Based on field investigation, the full-scale detail finite-element model, has established to calculate the dynamic behaviour of the vehicle in the accident. Then, the numerical simulation assists with the field investigation to identifying the structural weakness, which leading the injury of the occupant. Finally, an enhancement design for the structural weak point was considered to improve the vehicle crashworthiness in the same accident scenario.